2013
DOI: 10.1016/j.joca.2012.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in the HDL metabolic pathway predispose to the development of osteoarthritis in mice following long-term exposure to western-type diet

Abstract: Our findings suggest that perturbations in HDL metabolism predispose to OA following chronic insult with WTD and raise the challenging possibility that HDL has a causative relation to OA in patients with metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 38 publications
1
51
1
4
Order By: Relevance
“…2012), we were tempted to further explore the role of HDL in the pathobiology of OA. For this purpose we applied histological, histomorphomentrical and molecular/biochemical methodologies and found that after the consumption of Western-type diet both LCAT and APOA1 deficient mice developed OA, in contrast to the control groups (Triantaphyllidou et al 2013). This, suggests that alterations in HDL biogenesis and maturation predispose to the development of OA in mice, following chronic insult with Western-type diet.…”
Section: The Effect Of the Components Of The Hdl Metabolic Pathways Omentioning
confidence: 99%
See 1 more Smart Citation
“…2012), we were tempted to further explore the role of HDL in the pathobiology of OA. For this purpose we applied histological, histomorphomentrical and molecular/biochemical methodologies and found that after the consumption of Western-type diet both LCAT and APOA1 deficient mice developed OA, in contrast to the control groups (Triantaphyllidou et al 2013). This, suggests that alterations in HDL biogenesis and maturation predispose to the development of OA in mice, following chronic insult with Western-type diet.…”
Section: The Effect Of the Components Of The Hdl Metabolic Pathways Omentioning
confidence: 99%
“…We have recently documented that in addition to its role in atheroprotection, APOA1 is also implicated in the development of non-alcoholic fatty liver disease as well as in the pathogenesis of osteoarthritis in mice (Karavia et al . 2012, Trantaphyllidou et al . 2013).…”
Section: The Effect Of the Components Of The Hdl Metabolic Pathways Omentioning
confidence: 99%
“…22 Our research group has studied the role of HDL metabolic pathway in the pathogenesis of several diseases including osteoarthritis. [23][24][25] In fact, we have recently shown that apoA-1-and LCAT-deficient mice develop osteoarthritis when stressed with high-fat diet. 25 Triggered by the current knowledge and our research data in the present study we examined whether apoA-1 deficiency, and thus severely impaired HDL synthesis, affects the differentiation of bone marrow MSC in vitro and/or bone quality in vivo.…”
mentioning
confidence: 99%
“…[23][24][25] In fact, we have recently shown that apoA-1-and LCAT-deficient mice develop osteoarthritis when stressed with high-fat diet. 25 Triggered by the current knowledge and our research data in the present study we examined whether apoA-1 deficiency, and thus severely impaired HDL synthesis, affects the differentiation of bone marrow MSC in vitro and/or bone quality in vivo. Interestingly, we uncovered that the ApoA-1-deficient mice are severely osteoporotic with a complex phenotype that implicates HDL as a requirement for normal cell-fate selection in MSC in bone.…”
mentioning
confidence: 99%
“…Global Ldlr deletion, the gene encoding the LDL receptor, which plays a key role in the sequestration of circulating LDL cholesterol had no effect on cartilage health in collagenase-induced OA following a high cholesterol diet, but promoted ectopic bone formation and synovitis-like changes [38]. Alternatively, the presence of HDL appears critical to preventing cartilage destruction and OA, based on evidenced of increased cartilage degeneration and OA in apolipoprotein A-I-deficient mice consuming a Western diet [39]. This model is further supported by data from the investigation of hypercholesterolemia on the progression of OA, using a mouse model that closely mimics human lipoprotein metabolism and dyslipidemia.…”
Section: The Big Fat Metabolic Messmentioning
confidence: 99%